Artificial intelligence in games - Roberts, Paul; Dent, Nicholas (London, CRC Press, 2023)
"This book covers all the necessary topics that a professional game AI programmer needs to know, from math and steering behaviours to terrain analysis, pathfinding, decision making, and more. Written to be easily accessible, each topic is accompanied by an example game, where the reader can add their own code to see the effects their changes have. This book will be suitable for students and aspiring games programmers looking to gain a grounding in game AI techniques"--
Math -- Steering behaviours -- Terrain analysis -- Pathfinding -- Decision making -- Fuzzy logic -- Chess AI -- Genetic algorithms -- Neural networks.
Includes bibliographical references and index.
Keywords: Video games; Video games; Artificial intelligence